2014
DOI: 10.1016/j.bbamem.2013.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic activity of the boronated chlorin e6 amide in artificial and cellular membranes

Abstract: Photodynamic tumor-destroying activity of the boronated chlorin e6 derivative BACE (chlorin e6 13(1)-N-{2-[N-(1-carba-closo-dodecaboran-1-yl)methyl]aminoethyl}amide-15(2), 17(3)-dimethyl ester), previously described in Moisenovich et al. (2010) PLoS ONE 5(9) e12717, was shown here to be enormously higher than that of unsubstituted chlorin e6, being supported by the data on much higher photocytotoxicity of BACE in M-1 sarcoma cell culture. To validate membrane damaging effect as the basis of the enhanced tumori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Here, we for the first time applied boronated chlorin e 6 amide (BACE, chlorin e 6 13(1)-N-{2-[N-(1-carba-closo-dodecaboran-1-yl)methyl]aminoethyl}amide-15(2), 17(3)-dimethyl ester) [ 8 , 9 ] for aPDI and found this photosensitizer to show much higher efficacy against Gram-positive than against Gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we for the first time applied boronated chlorin e 6 amide (BACE, chlorin e 6 13(1)-N-{2-[N-(1-carba-closo-dodecaboran-1-yl)methyl]aminoethyl}amide-15(2), 17(3)-dimethyl ester) [ 8 , 9 ] for aPDI and found this photosensitizer to show much higher efficacy against Gram-positive than against Gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The sodium salt of BACE, synthesized as described earlier [33], was a gift from V.A.Ol'shevskaya (Nesmeyanov Institute of Organoelement Compounds, Russian Academy of Sciences). Chlorin e 6 was obtained from Porphyrin Products (Logan, UT).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the phenomenon of gA photodynamic inactivation, we developed a technique for estimating the photosensitizing and antioxidant efficacy through measurement of the degree of photodynamic inactivation of gA channels in planar bilayer lipid membranes (BLM) [24–30]. Bearing in mind the reduction of radiolytic inactivation of gA in unsaturated lipids [31], here we studied the effect of the double bond content on the gA photodynamic inactivation sensitized by the boronated chlorin e 6 derivative BACE (chlorin e 6 13(1)‐N‐{2‐[N‐(1‐carba‐closo‐dodecaboran‐1‐yl)methyl]aminoethyl}amide‐15(2), 17(3)‐dimethyl ester) – a recently found, very effective agent for PDT [32,33], and compared the results with the corresponding influence of unsaturated lipids on gA channels in the case of the t ‐BOOH addition.…”
Section: Introductionmentioning
confidence: 99%
“…This model system proved very useful for ana lyzing different properties of photosensitizers [17 21]. We recently showed that unsaturated lipids protect the gram icidin A peptide from photodynamic damage in the pres ence of boronated chlorin e 6 derivative (BACE [22]) and that the degree of protection increases with increasing number of double bonds in the lipid [23]. In this work, we studied the dependence of unsaturated lipid and ascor bate antioxidant activity on the photosensitizer mem brane immersion depth through the example of grami cidin photoinactivation in planar bilayer lipid membrane (BLM).…”
mentioning
confidence: 99%